2013
DOI: 10.1111/j.1532-950x.2013.01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Septic Arthritis After Elective Equine Arthroscopy Without Antimicrobial Prophylaxis

Abstract: Joint infection rate in the horse population that had elective arthroscopy without antimicrobial prophylaxis compares favorably with other reports citing 0.9% sepsis in horses after arthroscopy in which horses received either no antimicrobials or were administered pre or perioperative antimicrobial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 16 publications
8
74
0
Order By: Relevance
“…There are no standard guidelines for perioperative prophylaxis in horses or data that indicate a requirement for perioperative prophylaxis for arthroscopy. While this study was not designed to assess the efficacy of perioperative prophylaxis, the 0.67% SSI rate is comparable to previously reported rates of 0.14%–1.5% and the 0% rate reported in the previous study at this institution . Care must be taken when comparing studies; however, it is important to note that a study reporting a 0.7% infection rate after arthroscopy involved 444 horses, none of which received any antimicrobials .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There are no standard guidelines for perioperative prophylaxis in horses or data that indicate a requirement for perioperative prophylaxis for arthroscopy. While this study was not designed to assess the efficacy of perioperative prophylaxis, the 0.67% SSI rate is comparable to previously reported rates of 0.14%–1.5% and the 0% rate reported in the previous study at this institution . Care must be taken when comparing studies; however, it is important to note that a study reporting a 0.7% infection rate after arthroscopy involved 444 horses, none of which received any antimicrobials .…”
Section: Discussionsupporting
confidence: 82%
“…In man, there has been extensive study of the requirement for perioperative antimicrobial prophylaxis for arthroscopy, and antimicrobials are not typically recommended . There have been fewer evaluations in horses, and a protective effect of perioperative antimicrobials for prevention of septic complications in clean arthroscopic surgeries has not identified …”
Section: Introductionmentioning
confidence: 99%
“…A larger number of procedures would need to be examined to explore this relationship further. Interestingly, studies on equine surgery showed no difference in SSI when antibiotics were or were not used, and were all minimally invasive surgeries . Minimally invasive procedures in our study were associated with fewer glove perforations.…”
Section: Discussionmentioning
confidence: 45%
“…Although there is evidence from the human literature that the prophylactic administration of antimicrobials is unnecessary for most clean procedures , there is limited information relating to equine surgery. One study suggested that the omission of antimicrobial prophylaxis in elective arthroscopies did not increase the rate of synovial sepsis; however, further controlled studies are required to confirm this finding in different settings and rule out an increase of distant infections.…”
Section: Discussionmentioning
confidence: 99%